Rheological Findings on Storage Stability for Chemically Dispersed Crumb Rubber Modified Bitumen. (25th October 2021) - Memon, Naeem Aziz; Yusoff, Nur Izzi Md.; Jafri, Syed Faraz; Sheeraz, Khawaja
Graphical abstract: Highlights: Evaluations are being carried out to inculcate the idea of good dispersion of CR particles ensuring storage stability of bitumen. The blends are strengthened considering its reproduction with Dodecenyl Succinic Anhydride (DDSA) catering the poor characteristics of polymer. Testing protocols correspond on varying rheological properties with the focus on standouts blending conditions and material constituents. Major contribution includes stability of improper polymer dispersion with the perspective of an emerging material; Chemically Dispersed Crumb Rubber Modified Bitumen (CD-CRMB). The direct findings may proportionate to the assessment of fatigue life of mixture for said binders in the context of storage stability and X-Ray image analysis Abstract: Elastomers and different Plastomers are most common additives used to improve the performance of binder. However, bitumen modified with these additives is known to be unstable followed by the problem of separation. The separation problem becomes worse, when bitumen is modified with CR, which can undergo a high degree of phase separation during hot storage. The incorporation of CR reclaimed from waste tyres resulted in enhanced properties of conventional bitumen but with limited constraints. Scrap tyres is taken as important product followed by its effective use with virgin bitumen in order to rectify the mechanical and performance properties of base bitumen. The changes in densities of material constituents also affected the storage stability of blends. It is also dependent on the phase separation and dispersion of CR particles for storage intervals. The improved storage stability was attributed to a good CR dispersion which was also observed during softening point and X-Ray image analysis resulting into improved performance for experimented temperatures. Besides, the involvement of DDSA imparted with the significant change in the performance of blends against storage stability. The study is based on empirical techniques to be adopted as revolutions for smart and sustainable pavement materials.